Risvegli di primavera. Metamorfosi del ‘topos’ primaverile nell’«Inamoramento de Orlando» - Angelo Pietro Caccamo (Griseldaonline)
In the Inamoramento of Orlando, spring assumes a complex set of rhetorical and ideological functions. The locus amoenus is depicted as a spring landscape, following a codified tradition, as seen in the Riviera d'Amore (1, iii 37) and in the disturbing gardens of Dragontina (1, vi 48) and Falerina (2, iv 22). This contribution aims to highlight the exploitation of this theme in the Inamoramento, pointing out the different functions and meanings for which it is reused over time. Through the enchanted gardens, Boiardo develops a complex erotic theory, where the verger becomes, at times, a manifestation of a civilizing tension called Love, and at other times, a deceptive trap that reveals the possible consequences of an overwhelming passion. Finally, by assuming the form of the topos of the Golden Age, spring also conveys an ideological operation, as Boiardo announces a civil, ethical, and political renaissance under the new era of Ercole d’Este.